Experimental, Numerical and Analytical Characterization of Torsional Disk Coupling Systems - (:unkn) unknown (My University, 2014)
Torsional couplings are used to transmit power between rotating components in various power systems while allowing for small amounts of misalignment that may otherwise lead to equipment failure. When selecting a proper coupling type and size, one has to consider three important conditions: (1) the maximum load applied to the coupling, (2) the maximum operation speed, and (3) the amount of misalignment allowable for normal operation. There are many types of flexible couplings that use various materials for the flexible element of the coupling. The design of the coupling and the materials used for the flexible portion will determine its operating characteristics. In this project, investigation of a disk coupling that uses a stack of metallic discs to counter the misalignment effects is performed. Benefits of this type of coupling include: ease of replacement or repair, clear visual feedback of element failure, and the absence of a need for lubrication. The torsional stiffness of a coupling is a major factor relative to the amount of misalignment allowable. Currently, flexible couplings are tested by manufacturers to experimentally determine the torsional stiffness; a process which requires expensive equipment and more importantly employee time to set-up and run. The torsional coupling lumped characteristics, such as torsional- and flexural stiffness, as well as natural frequencies are important for design of the entire power system and have to be as precise as possible. In this work, we have developed an accurate modeling framework for determining these parameters based on a full 3-D finite element model and model-order reduction procedure. Developed methodology was validated by available experimental data from a regional manufacturer of torsional couplings.
Keywords: Disc Coupling; Finite Element; Flexible Coupling; Misalignment; Reduced Order Modeling; Torsional Stiffness